Is Covid-19 Severity Associated With ACE2 Degradation? - Bastolla, Ugo; Chambers, Patrick; Abia, David; Garcia-Bermejo, Maria-Laura; Fresno, Manuel (Frontiers in Drug Discovery, 2022)
Covid-19 is particularly mild with children, and its severity escalates with age. Several theories have been proposed to explain these facts. In particular, it was proposed that the lower expression of the viral receptor ACE2 in children protects them from severe Covid-19. However, other works suggested an inverse relationship between ACE2 expression and disease severity. Here we review the seemingly contradicting observations on ACE2 expression at the levels of mRNA, membrane protein and serum protein in humans and rodents and reconcile them at the light of the Renin-Angiotensin system (RAS) and bradykinin system, which constitute an integrated inflammatory system connected by common peptidases and interacting receptors. We find that ACE2 level does not vary monotonically but it reaches a cell-type dependent maximum at young age and then decreases, consistently with most existing data. The increase with age of the protease ADAM17, also known as TACE (Tumor necrosis factor alpha converting enzyme), that sheds ACE2 from the cell membrane to the serum predicts that the decrease occurs before and is steeper for ACE2 cell protein than for its mRNA. This negative relation between ACE2 level and Covid-19 severity at old age is not paradoxical but it is consistent with a mathematical model that predicts that higher viral receptor does not necessarily favour virus propagation and it can even slow it down. More importantly, the angiotensin-bradykinin system is characterized by a powerful positive feedback loop that enhances inflammation through the Angiotensin and Bradykinin receptors that upregulate ADAM17, which in turn downregulates ACE2 and upregulates TNF-$α$ and the pro-inflammatory receptor of the cytokine interleukin 6 (IL6). Here we propose that ACE2 contributes essentially to reverse this inflammatory state by downregulating the pro-inflammatory peptides of the angiotensin-bradykinin system, and that failure to do this, possibly induced by the degradation of ACE2 by SARS-COV-2, may underlie severe CoViD-19 and its post-infection manifestations, including the multi-inflammatory syndrome of children (MIS-C). Within this view, lower severity in children despite lower ACE2 expression may be consistent with their higher expression of the alternative angiotensin-II receptor ATR2 and in general of the anti-inflammatory arm of the RAS.